BIMBINGAN TEKNIS DIVERSIFIKASI PANGAN BERBAHAN DASAR IKAN DI DESA HUNUTH DURIAN PATAH KECAMATAN TELUK AMBON - Lalopua, Vonda Milca N.; Lokollo, Eder (Pattimura University, 2024)
Diversification is a variety of types of processed fishery products from raw materials that have not been/have been utilized. Diversification will provide variations in the food consumed so that you are not attracted to just one type. Fish-based food diversification is an effort to increase consumption of fishery products in terms of quality, quantity and increase in selling value. The aim of this PKM is to provide training on fish-based food diversification for groups of women residents of Hunuth Durian Patah Village, Teluk Ambon District. It is hoped that this activity will be a stimulus to increase people's creativity in processing fish to add value to products. The implementation method is carried out with lectures about diversification, objectives and benefits, nutritional content of fish, fish-based diversified products and the practice of making fish nuggets. The media used are questionnaires, power points, test sheets (pre and post test) and organoleptic assessment sheets. The post test results showed an increase in knowledge about making fish nuggets. Community Service Activities have a positive impact on promoting the diversity of processed forms of fish for programs to accelerate fish food consumption.